Long-Term Evaluation of Ocular Surface and Meibomian Gland Function after Laser-Assisted in situ Keratomileusis Surgery - Kenneth Ka Hei Lai; Zhichao Hu; Jamie Tsun Chiu; Fatema Mohamed Ali Abdulla Aljufairi; Jake Uy Sebastian; George Pak Man Cheng; Wilson Wai Kuen Yip; Alvin Lerrmann Young; Clement Chee Yung Tham; Calvin Chi Pui Pang; Kelvin Kam Lung Chong (Ophthalmic Research)
Introduction: Laser-assisted in situ keratomileusis (LASIK) is a common refractive surgery. But it may lead to temporary dry eye due to reversible damage to the corneal subbasal nerve plexus. However, evidence on chronic ocular surface changes are unclear. This study reports the ocular surface changes, partial blinking rates, and meibomian gland statuses in eyes that underwent LASIK for at least 48 months. Methods: Cross-sectional, matched case-control comparison study, including 48 post-LASIK patients and 48 sex-, age-, smoking-, and axial length-matched healthy controls, recruited from a community eye screening program. Outcome measures include anterior segment clinical findings, keratographic and meibographic imaging. Results: Totally, 48 right eyes of 48 post-LASIK Chinese patients (39 females, 2 smokers) were analyzed with 48 right eyes of 48 matched healthy controls. The mean age at the time of ocular surface examination was 50 ± 11 years, and the axial length 26±1 mm. Post-LASIK eyes had a lower quality of meibum (p = 0.008) compared to healthy controls. Post-LASIK eyes were associated with a shorter Schirmer's test (p = 0.03). The ocular surface disease index (OSDI) score was higher in post-LASIK patients (p = 0.00001). Other anterior segment examination parameters, partial blinking rate, meibomian gland dropout, lipid layer thickness, noninvasive tear break-up time, and tear meniscus height were comparable between the 2 groups. Conclusions: Up to 75% of post-LASIK patients complained of on-going, chronic dry eye symptoms. Post-LASIK eyes were associated with a reduced aqueous tear production. Post-LASIK patients with chronic dry eye symptoms are advised to have periodic ocular surface evaluation. Treatments might be considered in patients with poor tear film stability.